Prospek Tanaman Obat sebagai Antihepatitis - Yunarto, Nanang (Jurnal Kefarmasian Indonesia, 2013)
Hepatitis remains a serious global health problem because of the potential impact to morbidity and mortality. Prevalence of hepatitis patients in Indonesia either by viral infection or noninfection increases rapidly. The high cost of treatment hepatitis resulted in the switch in the use medicinal plants to cope with this disease. Several types of medicinal plants were proven to be antihepatitis such as meniran, temulawak, mengkudu and pegagan. The objective of this paper is to provide scientific information study of medicinal plants useful as antihepatitis and their development prospect. The method used in this study is to review the relevant scientific articles in international and national journals. Based on reference studies it has been reported that meniran, temulawak, mengkudu and pegagan have a great potential and prospective as antihepatitis drugs. The important challenge in development of medicinal plants is a constant quality as well as, continuous supply of raw materials and effect assured.